Vapor–liquid partitioning of alkaline earth and transition metals in NaCl-dominated hydrothermal fluids: An experimental study from 360 to 465 °C, near-critical to halite saturated conditions. (1st November 2015) - Pester, Nicholas J.; Ding, Kang; Seyfried, William E.
Abstract: Multi-phase fluid flow is a common occurrence in magmatic hydrothermal systems; and extensive modeling efforts using currently established P–V–T–x properties of the NaCl–H2 O system are impending. We have therefore performed hydrothermal flow experiments (360–465 °C) to observe vapor–liquid partitioning of alkaline earth and first row transition metals in NaCl-dominated source solutions. The data allow extraction of partition coefficients related to the intrinsic changes in both chlorinity and density along the two-phase solvus. The coefficients yield an overall decrease in vapor affinity in the order Cu(I) > Na > Fe(II) > Zn > Ni(II) ⩾ Mg ⩾ Mn(II) > Co(II) > Ca > Sr > Ba, distinguished with 95% confidence for vapor densities greater than ∼0.2 g/cm 3 . The alkaline earth metals are limited to purely electrostatic interactions with Cl ligands, resulting in an excellent linear correlation ( R 2 > 0.99) between their partition coefficients and respective ionic radii. Though broadly consistent with this relationship, relative behavior of the transition metals is not well resolved, being likely obscured by complex bonding processes and the potential participation of Na in the formation of tetra-chloro species. At lower densities (at/near halite saturation) partitioning behavior of all metals becomes highly non-linear, where M /Cl ratios in the vapor begin to increase despite continued decreases in chlorinity and density. We refer to this phenomenon as "volatility", which is broadly associated with substantial increases in the HCl/NaCl ratio (eventually to >1) due to hydrolysis of NaCl. Some transition metals (e.g., Fe, Zn) exhibit volatility prior to halite stability, suggesting a potential shift in vapor speciation relative to nearer critical regions of the vapor–liquid solvus. The chemistry of deep-sea hydrothermal fluids appears affected by this process during magmatic events, however, our results do not support suggestions of subseafloor halite precipitation recorded in currently available field data. Ca–Cl systematics in vent fluids are specifically explored, revealing behavior consistent with partitioning due to phase separation. Interestingly, the effect of variable chloride on dissolved Na/Ca ratios associated with plagioclase solubility (in single-phase solutions) appears fundamentally similar to that of phase separation on vapor compositions such that vapors evolved in hydrothermal systems may naturally remain near equilibrium with the host lithology. Conversely, residual liquids/brines left behind in the crust may be undersaturated with metals, enhancing the rate and extent of hydrothermal alteration.